Beyond Participation and Stereotypes: Towards the Study of Engagement in Adult Literacy Education - B. Allan Quigley (Adult Education Research Conference, 2000)
Mainstream adult education framed the critical issues of literacy non-participation within its normative participation models creating a serious setback for literacy. Research. Through a review of the literacy literature and an analysis of the IALS and NALL studies, this paper discusses how undereducated adults refuse to participate in formal education, yet how they engage in informal and incidental learning. It concludes with an argument for research into how and why the undereducated engage in learning rather than participate in education.